Educação e desigualdade de renda no Brasil - Pinto, Isabela Freire de Andrade (2017)
In this study, we seek to understand the degree in which education can affect income inequality in Brazil. We analyzed the Gini index at state level, taking into account the average years of schooling, educational inequality and percentage of enrollment in each educational stage. We developed the educational inequality index and we insert control variables as the minimum wage, informality and unemployment rate. We estimated four models in panel data: Fixed Effects, Random Effects, Weighted Least Squares and Cluster Estimator. The results show that education generates a significant impact on the income inequality. The enrollment in High School has a greater, and also statistically significant effect, on the income inequality in three models. Finally we conclude that education affects income inequality in Brazil and the increase of 1% of the population with complete secondary education, drops the Gini index by 0,003 p.p.